2010
DOI: 10.2298/tsci091113001t
|View full text |Cite
|
Sign up to set email alerts
|

Development of the boiler for combustion of agricultural biomass by products

Abstract: Republic of Serbia consumes about 15 million tons of equivalent oil per year (Mtoe). At the same time potential of the renewable energy sources is about 3,5 Mtoe/year. Main renewable source is biomass, with its potential of about 2,6 Mtoe/year, and 60% of the total biomass source is of agricultural origin. Mainly, that type of biomass is collected, transported and stored in form of bales. At the same time in one of the largest agricultural companies in Serbia (PKB) there are over 2000 ha of soya plantations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Verified scientific results, realized during these investigations, were made throughout the preparation of master and doctoral theses [5][6][7][8][9], the publication of scientific papers in international journals, several are placed in references [10][11][12][13][14][15][16][17][18], as well as preparation of studies [4,19].…”
Section: Methodology Of the Development Process Of Combustion Of Solimentioning
confidence: 99%
“…Verified scientific results, realized during these investigations, were made throughout the preparation of master and doctoral theses [5][6][7][8][9], the publication of scientific papers in international journals, several are placed in references [10][11][12][13][14][15][16][17][18], as well as preparation of studies [4,19].…”
Section: Methodology Of the Development Process Of Combustion Of Solimentioning
confidence: 99%
“…The key finding is a series of guidelines to achieve the challenging 'Energy in Future City' scenario. The relation between the farming sector and energy has been discussed in previous research such as [103] where the potential for the utilisation of biogas was demonstrated and [104] where the use of agricultural biomass in CHP has been presented on a study for Serbia. In another case study [105] the effect of increases in electricity costs on 58 farming communities in north-eastern Spain are investigated and changes in the current tariff structure as well as increases in articles, such as energy intensity, with all the positive and negative aspects of using it [107].…”
Section: Case Studies Policy and The Environmentmentioning
confidence: 99%
“…The principle of operation of facilities with cigarette burner system (CBS) can be found in papers [17][18][19]. An industrial-scale hot water boiler at Fig.…”
Section: Description Of the Experimental Facilitiesmentioning
confidence: 99%